Nitrogen addition restricts key soil ecological enzymes and nutrients by reducing microbial abundance and diversity - Li, Xiaodong; Su, Lianbo; Jing, Ming; Wang, Keqin; Song, Chenggong; Song, Yali (Scientific reports, 2025)
Microorganisms are critical in forest ecosystems, where they secrete soil ecological enzymes and mediate nutrient cycling. These processes are essential in determining how these ecosystems respond to nitrogen (N) addition inputs. In this study, an N addition experiment was conducted with three levels of N addition treatments in a subtropical evergreen broad-leaved forest in southwest China. The aim was to identify the effects of low (LN: 10 g m − 2 year −1 ), medium (MN: 20 g m − 2 year − 1 ), and high N addition (HN: 25 g m − 2 year − 1 ) on soil microbial community structure, diversity, ecological enzyme activities, and nutrient content, and to explore whether and how soil microorganisms influence ecological enzyme activity and nutrient cycling. Our observations indicated that surface soil exhibited the highest microbial diversity, ecological enzyme activities, and nutrient contents. N addition led to a reduction in soil bacterial and fungal diversity, with bacterial diversity consistently higher than fungal diversity. Moreover, bacterial community structures were generally more diverse and complex compared to fungal communities. The study emphasized that bacteria were relatively enriched under LN treatment, while fungi exhibited higher relative abundance under control conditions. Different soil microbial groups exhibited distinct responses to N addition, with an inhibitory effect on enzyme activities such as invertase (Inv), urease (Ure), and acid phosphatase (ACP), and an enhancement of catalase (CAT) activity. With increasing N addition levels, soil organic carbon (SOC), total N (TN), and total phosphorus (TP) contents decreased, whereas total potassium (TK), nitrate N (NO 3 − -N), and ammonium N (NH 4 + -N) exhibited the opposite trend. Co-linearity network analysis revealed stronger interactions among soil bacteria compared to fungi. The dominant bacterial phyla Pseudomonadota and Verrucomicrobiota showed stronger correlations with Ure and ACP, respectively, while Acidobacteriota exhibited a higher correlation with TP. Among the dominant fungal phyla, Basidiomycota had stronger correlations with CAT, NO 3 − -N, and NH 4 + -N, while Ascomycota was notably associated with Inv. The results showed that soil bacteria had a strong correlation with ecological enzymes, while soil fungi had a strong correlation with nutrients. This implies that bacteria and fungi have distinct advantages in enzyme secretion and nutrient mediation, leading to a trend of nutritional complementarity.